Kinerja Pegawai Bagian Persidangan Dan Perundang-Undangan Di Protokoler Sekertariat Dewan Perwakilan Rakyat Daerah (Dprd) Kabupaten Landak - Lisa Yulita; Azrita Mardhalena; Yulius Yohanes (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to analyze the performance of protocol officers in the Legislative and Regulatory the Public Relations Department at the Secretariat of the Regional House of Representatives (DPRD) of Landak Regency. The research focuses on the implementation of the Work Plan and Budget System (RKAKL), designed to enhance efficiency and effectiveness in the DPRD work environment. Using a descriptive qualitative approach, this study explores how employees perform their duties, the challenges they face, and the supporting factors influencing the successful implementation of this system.The findings reveal that the implementation of RKAKL has not yet been fully optimized. Employees often encounter challenges, such as limited technical understanding of the system, inadequate supporting facilities, and ineffective supervision. However, there are initiatives from leadership to create a more conducive work environment through employee welfare policies and training programs. While the results are not yet maximized, these efforts have positively impacted employee motivation.This study recommends enhancing training programs, providing adequate work facilities, and adopting results-based evaluations as strategic measures to optimize employee performance. These findings are expected to contribute to public sector human resource management, particularly in supporting better governance at the regional level.